The impact of Cannabidiol on the frequency of convulsive seizures in patients with Dravet Syndrome compared to the use of Clobazam: A systematic review (Research, Society and Development, 2024)
Dravet Syndrome (DS) is an epileptic encephalopathy that presents itself as drug-resistant, commonly diagnosed in childhood, that is the reason for issues in cognition and child development. On account of being a drug-resistant illness, alternative options and treatment for adjuvant therapy have been suggested as an alternative with the aim of a better seizure management and quality of life for the patient. The present systematic review, aims to evaluate the efficacy of Cannabidiol in comparison with Clobazam on the reduction in seizure frequency in patients diagnosed with DS. Therefore, in a cautious analysis of the articles related to Dravet Syndrome, Cannabidiol and Cloazam, published in the PUBMED database, between 2019 and 2024, 9 articles were selected. Upon the data, it was possible to assess that both Cannabidiol and Clobazam were effective as adjuvants in treatment of Dravet Syndrome, which is drug-resistant, in addition to demonstrating acceptable tolerability and toxicity, even though it has greater adverse effects with the adjuvant treatment.